(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Medicinal chamomile (Matricaria chamomilla) belongs to the Asteraceae family and has a place in the pharmaceutical, cosmetic, perfumery, personal care and beverage industries. Due to the high value of medicinal chamomile essential oil in the world market, it is often cultivated for commercial purposes.